Morpho-anatomical and nrITS based identification of Lactarius swaticus (Russulaceae, Russulales) from Pakistan: An addition to the global mycoflora - Sana; Kiran, Munazza (Phytotaxa, 2025)
A new species, Lactarius swaticus is described based on collections from the Swat District, Pakistan. Morphological data and phylogenetic analysis based on nrITS sequence supported that the species is undescribed. Lactarius swaticus is characterized by yellow-orange to orange colored basidiomata, planoconvex, umbilicate pileus with smooth crenate margins, ventricose lamellae, globose to broadly ellipsoid, partial to nearly complete reticulated basidiospores measuring on average 6.11 × 5.35 μm, narrowly clavate to clavate marginal cells, an irregular trichoderm pileipellis and absence of leptocystidia and pleuromacrocystidia. This paper presents detailed morphological descriptions, illustrations, and phylogenetic analysis of L. swaticus based on nrITS sequence along with a comparative analysis with related species.